Effects of nanofeatures induced by severe shot peening (SSP) on mechanical, corrosion and cytocompatibility properties of magnesium alloy AZ31. (15th January 2018) - Bagherifard, Sara; Hickey, Daniel J.; Fintová, Stanislava; Pastorek, Filip; Fernandez-Pariente, Ines; Bandini, Michele; Webster, Thomas J.; Guagliano, Mario
Graphical abstract: Abstract: The application of biodegradable magnesium-based materials in the biomedical field is highly restricted by their low fatigue strength and high corrosion rate in biological environments. Herein, we treated the surface of a biocompatible magnesium alloy AZ31 by severe shot peening in order to evaluate the potential of surface grain refinement to enhance this alloy's functionality in a biological environment. The AZ31 samples were studied in terms of micro/nanostructural, mechanical, and chemical characteristics in addition to cytocompatibility properties. The evolution of surface grain structure and surface morphology were investigated using optical, scanning and transmission electron microscopy. Surface roughness, wettability, and chemical composition, as well as in depth-microhardness and residual stress distribution, fatigue behaviour and corrosion resistance were investigated. Cytocompatibility tests with osteoblasts (bone forming cells) were performed using sample extracts. The results revealed for the first time that severe shot peening can significantly enhance mechanical properties of AZ31 without causing adverse effects on the growth of surrounding osteoblasts. The corrosion behavior, on the other hand, was not improved; nevertheless, removing the rough surface layer with a high density of crystallographic lattice defects, without removing the entire nanocrystallized layer, provided a good potential for improving corrosion characteristics after severe shot peening and thus, this method should be studied for a wide range of orthopedic applications in which biodegradable magnesium is used. Statement of Significance: A major challenge for most commonly used metals for bio-implants is their non-biodegradability that necessitates revision surgery for implant retrieval when used as fixation plates, screws, etc. Magnesium is reported among the most biocompatible metals that resorb over time without adverse tissue reactions and is indispensable for many biochemical processes in human body. However, fast and uncontrolled degradation of magnesium alloys in the physiological environment in addition to their inadequate mechanical properties especially under repeated loading have limited their application in the biomedical field. The present study provides data on the effect of a relatively simple surface nanocrystallziation method with high potential to tailor the mechanical and chemical behavior of magnesium based material while maintaining its cytocompatibility.